Lo cotidiano: una forma básica de mirar la diversidad - Hernández Vargas, Dora María (Revista Electrónica Educare, 2007)
By using a fragment of Jorge de Bravo’s poem, the author of this essay takes the reader into a journey of thinking about the significance of how respect for human diversity must be approached on a daily basis, since a regular need for tenderness, supper, silence, bread and home.Our well-known poet makes one of the most consistent and vigorous statements that I can think of when he writes with poetic beauty, like if all humankind would say with him: “I am a man, I was born, I have skin and hope…”. Debravo manages to express and identify remarkably powerfully in this brief poem, some of the basic people’s rights and needs. In what I consider the major fragment of his poem he says: “I do not ask for eternities full of white stars”. Then, he gently explains: “I ask for tenderness, supper, silence, bread and home…”.